Devaluing and Revaluing Women: A Feminist Approach to Chandra Prakash Baniya’s Maharani [Queen] - Singh, Ajita; Thakur, Ram Sebak (The Outlook: Journal of English Studies, 2024)
Chandra Prakash Baniya's Maharani [Queen] is a telling tale of women's exploitation and their glass ceiling in a male dominated society. The novel depicts how women are either risen to the pedestal of ‘Goddess’ or devalued to the position of a ‘whore’, but never given a genuine respect. By aggrandizing or derogating the status of women, the patriarchal society has always subordinated, subjugated, and exploited them. The scenario of deprivation of women from attaining their rights is the main concern of the novelist. He suggests that the prevalence of biased treatment for women in every sphere - social, economic, political, literary - is rampant, and from getting secondary position to being thwarted to grow is an unfortunate fate meted out to women in this male-dominated society. Patriarchy, therefore, has become a clog in the route of women's progress. The present paper aims at exploring the pathetic condition of women in the novel, discussing how women become the victim of glass ceiling in a social labyrinth created by males. To address this objective, the study has employed feminism as a tool to examine the condition of women, especially drawing the concept of glass ceiling of women from Judith Butler to interpret the text.